PERINGATAN HARI BESAR ISLAM DALAM MENINGKATKAN SIKAP KEBERAGAMAN MASYARAKAT DI DESA CIDENOK: The Commemoration Of Islamic Holy Day In Increasing Community's Attitude Of Diversity In Cidenok Village - Dhea Herdianti; Defit Mila Uswatun Nisa; Kusniah Kusniah; Dede Puadah; Rizqi Alviandi; Aar Suhendi; Annisa Marinovte Rahmatillah; Lanlan Muhria (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The implementation of this service activity is focused on Cidenok Village with a program to improve the quality of community religion. This devotion is the main concern to pay more attention to the field of spirituality, because in this village there are several prayer rooms in each block so that spiritual activities in Cidenok Village already sound familiar, with regular recitation in each block which is held once a week. In addition, it also aims to develop the creativity of Cidenok Village children in the field of spirituality. This is in accordance with the purpose of education, one of which is in efforts to build character. This service is carried out with an Asset Based Community Development (ABCD) approach. The Community Service Program in Cidenok Village can be carried out well and run smoothly. The results of this service show that the momentum of commemorating Islamic holidays through various religious competition activities has a positive impact in improving the religious attitude of the people of Cidenok Village. For this reason, efforts that can be made to further empower the younger generation and Muslim society in general are increasing the intensity and quality of religious programs or activities that can be optimized through the commemoration of Islamic holidays.